2020
DOI: 10.1109/access.2020.3009644
|View full text |Cite
|
Sign up to set email alerts
|

A Deep Learning Based Fault Diagnosis Method With Hyperparameter Optimization by Using Parallel Computing

Abstract: Bearing fault diagnosis is of great significance to ensure the safe operation of mechanical equipment. This paper proposes an intelligent fault diagnosis method of rolling bearings based on deep belief network (DBN) with hyperparameter optimization by using parallel computing. Different with traditional diagnosis methods that extract the features manually depending on much prior knowledge about signal processing techniques and diagnostic expertise, DBN extracts fault features automatically by machine learning … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…The data used in this paper for experimental validation were provided by the Case Western Reserve University (CWRU), Cleveland, Ohio, USA [23]. As shown in Fig.…”
Section: Vibration Test Datamentioning
confidence: 99%
“…The data used in this paper for experimental validation were provided by the Case Western Reserve University (CWRU), Cleveland, Ohio, USA [23]. As shown in Fig.…”
Section: Vibration Test Datamentioning
confidence: 99%
“…Aktürk [22] has shown that the difficulty level of the minefield game can be increased and decreased at the desired level by using the genetic algorithm and pixelization method together. Guo et al [23] have proposed an intelligent diagnostic method for rolling bearings based on depth. The training speed has been improved by adapting the parallel computing to the DBN training process in order to achieve global optimization with the genetic algorithm and to achieve more successful results in diagnosis accuracy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Deep learning technology has shown good performance in fault detection and diagnosis with its powerful feature extraction ability and excellent classification performance, thus, it has become a research hotspot. Guo et al [11] proposed an intelligent method based on deep belief network (DBN) and hyperparameter optimization for fault diagnosis of rolling bearings. Li et al [12] proposed a deep autoencoder network for cross-machine fault diagnosis.…”
Section: Introductionmentioning
confidence: 99%